2018
DOI: 10.1080/1461670x.2018.1528880
|View full text |Cite
|
Sign up to set email alerts
|

Normative and Audience Discourses on Public Service Journalism at a “Critical Juncture”: the Case of TVE in Spain

Abstract: The concept of journalism, its metatheory and, in particular, public service journalism is regulated by feedback between political models (legal and normative framework), academic precepts and social practices. Scant attention has been paid to date to the impact that these models have on citizens' discourses, which is especially relevant at "critical junctures", i.e. periods in which the old institutions are collapsing and require renovation (McChesney, 2007). Hence, this paper addresses the issue in the Spani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Academic normative discourses and journalistic practices influence citizens’ discourses on journalism too, as our previous findings illustrate as regards Spanish viewers’ discourses (Lamuedra et al, 2018). As before, audience opinions not only have an impact on journalism in the shape of ‘expected expectations’ (Schmidt, 2008: 67).…”
Section: The Subject Of Voice and The Field Of Participatory Journalismmentioning
confidence: 53%
See 3 more Smart Citations
“…Academic normative discourses and journalistic practices influence citizens’ discourses on journalism too, as our previous findings illustrate as regards Spanish viewers’ discourses (Lamuedra et al, 2018). As before, audience opinions not only have an impact on journalism in the shape of ‘expected expectations’ (Schmidt, 2008: 67).…”
Section: The Subject Of Voice and The Field Of Participatory Journalismmentioning
confidence: 53%
“…In all the groups analysed, it was recognised that the media represented the voice and interests of ‘others’. What was involved was a sort of ‘super-subject’ with limitless political, economic and media power to whom the respondents often referred using the pronoun ‘them’ (Lamuedra et al, 2018). 6 And this led to visible frustration.…”
Section: Results: the Recognition Consent And Voice Of Citizens Accomentioning
confidence: 99%
See 2 more Smart Citations
“…An initial analysis of these three groups showed that they shared similar critical diagnoses and demands (see Lamuedra et al 2018;Lamuedra Graván et al 2020). In view of this, an attempt was made to determine whether or not these-and other-similarities in their discourses could be found in other social groups.…”
mentioning
confidence: 99%